Effect of Ti content on the wetting behavior of Sn0.3Ag0.7Cu/AlN system. (5th February 2017) - Fu, W.; Song, X.G.; Zhao, Y.X.; Cao, J.; Feng, J.C.; Jin, C.; Wang, G.D.
Abstract: In this work, the effect of Ti content on the wettability of Sn0.3Ag0.7Cu/AlN system was investigated by sessile drop method at elevating and isothermal process. Added Ti resulted in a significant reduction of contact angle. The lowest contact angle was obtained with 4%Ti addition possessing sufficient Ti and proper fluidity. Interfacial reaction product TiN promoted the spreading of droplet on AlN. However, the formed solid Ti-Sn intermetallics and dissolved Ti inhibited the spreading of droplet resulting in a higher contact angle. In wetting process, the rapid-decrease stage and the sluggish-decrease stage were limited by the kinetics of reaction at triple line and the diffusion of Ti to the triple line respectively. The speed of the spreading stage varied from 0.04°/s to 0.36°/s resulting from different operative temperature. Eventually, the wetting process of Sn0.3Ag0.7Cu/AlN system was schematized. Graphical abstract: Highlights: Effect of active Ti on the wettability of Sn0.3Ag0.7Cu/AlN system was investigated. Wetting process consisted of rapid-decrease stage and sluggish-decrease stage. Ti promoted the spreading of droplet by TiN formed by reaction between Ti and AlN. Solid Ti-Sn intermetallics and dissolved Ti inhibited the spreading of droplet.